Pendampingan UMKM dalam Pemasaran Online Melalui Media Sosial di Kotamobagu: Pengabdian - Maramis, Leonard; Varly Carnavale Wullur; Chandra Wisnu Nugroho; Ridwan Potabuga; Firmansyah Lanjani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to assist Micro, Small, and Medium Enterprises (MSMEs) in Kotamobagu in utilizing social media as a tool for product marketing. The background of this activity lies in the fact that many MSMEs still rely on conventional marketing methods, which limit their market reach. The implementation methods included socialization, training/workshops, technical assistance, and monitoring and evaluation. A total of 20 MSME participants from various business sectors were actively involved in this program. The results indicated an increase in participants’ knowledge of digital marketing, improved skills in creating business accounts and promotional content on social media, and an expansion of market reach through digital platforms. In conclusion, this program successfully enhanced the skills and competitiveness of MSMEs in facing the challenges of the digital economy era.